Comparison of two live Bacillus species as feed additives for improving in vitro fermentation of cereal straws. (27th November 2015) - Wang, Zuo; He, Zhixiong; Beauchemin, Karen A.; Tang, Shaoxun; Zhou, Chuanshe; Han, Xuefeng; Wang, Min; Kang, Jinhe; Odongo, Nicholas E.; Tan, Zhiliang
Abstract: This study was performed in a 2 × 4 factorial arrangement to explore and compare the effects of inclusion of two live Bacillus additives ( B. licheniformis and B. subtilis ) at four doses (0, 0.25 × 10 7, 0.50 × 10 7 and 0.75 × 10 7 colony‐forming units (cfu)) on in vitro gas production kinetics, fiber degradation, methane production and ruminal fermentation characteristics of maize stover and rice straw by mixed rumen microorganisms in dairy cows. The pH, concentrations of ammonia nitrogen (NH3 ‐N) and isovalerate were increased ( P < 0.05), while the methane (CH4 ) production, ratio of acetate to propionate, and total volatile fatty acids (TVFA) concentration were decreased ( P < 0.05) by the supplementation of B. licheniformis compared with that of B. subtilis . Adding B. licheniformis and B. subtilis raised ( P < 0.05) or numerically raised the maximum gas production, while decreasing ( P < 0.05) or numerically lowering pH and concentrations of most volatile fatty acids. The addition of B. licheniformis increased ( P < 0.05) the NH3 ‐N concentration but reduced CH4 production and ratio of acetate to propionate ( P < 0.05), while the NH3 ‐N concentration was decreased ( P < 0.05), and the CH4 production and ratio of acetate to propionate were increased by that of B. subtilis compared to the control. Results obtained in this research suggest that B. licheniformis would be preferred as a live Bacillus additive in comparison with B. subtilis, and its optimal dose should be 0.25 × 10 7 cfu/500 mg substrates.